Original paperThe impact of transcatheter aortic valve implantation on left ventricular performance and wall thickness – single-centre experience - Stokłosa, Patrycjusz; Szymański, Piotr; Dąbrowski, Maciej; Zakrzewski, Dariusz; Michałek, Piotr; Orłowska-Baranowska, Ewa; El-Hassan, Kamal; Chmielak, Zbigniew; Witkowski, Adam; Hryniewiecki, Tomasz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : Transcatheter aortic valve implantation (TAVI) is a treatment alternative for the elderly population with severe symptomatic aortic stenosis (AS) at high risk for surgical aortic valve replacement (SAVR). Aim : To assess the impact of TAVI on echocardiographic parameters of left ventricular (LV) performance and wall thickness in patients subjected to the procedure in a single-centre between 2009 and 2013. Material and methods: The initial group consisted of 170 consecutive patients with severe AS unsuitable for SAVR. Logistic European System for Cardiac Operative Risk Evaluation (EuroSCORE) was 21.73 ±12.42% and mean age was 79.9 ±7.5 years. Results: The TAVI was performed in 167 (98.2%) patients. Mean aortic gradient decreased significantly more rapidly after the procedure (from 58.6 ±16.7 mm Hg to 11.9 ±4.9 mm Hg, p < 0.001). The LV ejection fraction (LVEF) significantly increased in both short-term and long-term follow-up (57 ±14% vs. 59 ±13%, p < 0.001 and 56 ±14% vs. 60 ±12%, p < 0.001, respectively). Significant regression of interventricular septum diameter at end-diastole (IVSDD) and end-diastolic posterior wall thickness (EDPWth) was noted in early (15.0 ±2.4 mm vs. 14.5 ±2.3 mm, p < 0.001 and 12.7 ±2.1 mm vs. 12.4 ±1.9 mm, p < 0.028, respectively) and late post-TAVI period (15.1 ±2.5 mm to 14.3 ±2.5 mm, p < 0.001 and 12.8 ±2.0 mm to 12.4 ±1.9 mm, p < 0.007, respectively). Significant paravalvular leak (PL) was noted in 21 (13.1%) patients immediately after TAVI and in 13 (9.6%) patients in follow-up (p < 0.001). Moderate or severe mitral regurgitation (msMR) was seen in 24 (14.9%) patients from the initial group and in 19 (11.8%) patients after TAVI (p < 0.001). Conclusions : The TAVI had an immediate beneficial effect on LVEF, LV walls thickness, and the incidence of msMR. The results of the procedure are comparable with those described in other centres.